2019
DOI: 10.1016/j.rbmo.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian stimulation and endometriosis progression or recurrence: a systematic review

Abstract: In women with endometriosis, IVF does not generally increase the risk of disease recurrence. There is evidence, however, that intrauterine insemination may increase this risk and that deep peritoneal lesions may progress in some cases, although further studies are needed to confirm the latter findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 49 publications
1
22
1
1
Order By: Relevance
“…The impact of IVF on an endometriotic cyst seems to be mild. In their systematic review, Somigliana et al reported that IVF does not worsen endometriosis-related pain symptoms or increase the risk of endometriosis recurrence [42].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of IVF on an endometriotic cyst seems to be mild. In their systematic review, Somigliana et al reported that IVF does not worsen endometriosis-related pain symptoms or increase the risk of endometriosis recurrence [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, ovarian stimulation may cause some concerns among patients. Impact of ovarian stimulation on the progression of endometriosis or its recurrence was recently summarized in a systematic review [ 24 ]. According to their report, impact of ovarian stimulation on ovarian endometrioma, if present, is clinically unremarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Возможно, гормональная супрессия ведет к неполному удалению эндометриоидных очагов во время оперативного вмешательства, вызывая их атрофию и уменьшая в размерах [29]. Противоречивые данные имеются относительно связи рецидива ЭКЯ с предшествующим использованием препаратов для стимуляции яичников в программах ВРТ [30][31].…”
Section: факторы риска развития рецидива экяunclassified